A nap - Coan, Sharon (Huntington Beach, CA : Teacher Created Materials, 2012)
A family goes camping and takes a nap after setting up their tent.
Cover title.
"-ap"--Cover page [4].
"TCM 13927"--Cover page [4].
School Library Journal, April 2012
0.8
Preschool
Keywords: Naps (Sleep) -- Juvenile fiction; Camping -- Juvenile fiction; Naps (Sleep) -- Fiction; Camping -- Fiction; Naps (Sleep) -- Fiction; Camping -- Fiction; Readers (Elementary)